Role of JNK Signaling Pathway in Dexmedetomidine Post-Conditioning-Induced Reduction of the Inflammatory Response and Autophagy Effect of Focal Cerebral Ischemia Reperfusion Injury in Rats - Zhu, Yulin; Li, Shihong; Liu, Jingying; Wen, Qing; Yu, Jingui; Yu, Lingzhi; Xie, Kun (Inflammation, 2019)
To investigate the effect of dexmedetomidine post-conditioning on the inflammatory response and autophagy effect of focal cerebral ischemia reperfusion injury in rats, and further to study its potential mechanisms. Water maze was conducted to evaluate spatial learning and memory ability of middle cerebral artery occlusion (MCAO) rats. TTC staining was used to observe the area of cerebral infarction. The expressions of inflammatory factors in serum were detected by ELISA. TUNEL assay, HE staining, and transmission electron microscopy were used to detect the apoptosis of neurons, neuro-cytopathic changes, and the formation of auto-phagosome in hippocampus CA1 region, respectively. The mRNA and protein expression of Beclin-1, Caspase-3, and light chain 3 (LC3) were detected by qRT-PCR and Western blot. Moreover, the activity of C-Jun N-terminal kinase (JNK) pathway was detected by Western blot. The escape latency (EL); cerebral infarction area ratio; positive apoptosis; neuron pathological changes; auto-phagosome numbers; inflammatory factor contents; mRNA and protein expressions of Beclin-1, Caspase-3 and LC3II/I; and the phosphorylation level of JNK were decreased, while the times across platform and the times stayed in the quadrant of the original platform were increased after dexmedetomidine treatment. However, the protective effect of dexmedetomidine on brain injury in MCAO rats was reversed by JNK pathway activator. Dexmedetomidine post-conditioning could improve learning and memory dysfunction caused by MCAO in rats and reduce the inflammatory response and autophagy effect. The mechanism may be related to inhibition of JNK pathway activation.